Epidemiology and management of hepatitis C virus infections in immigrant populations - Nicola Coppola; Loredana Alessio; Lorenzo Onorato; Caterina Sagnelli; Margherita Macera; Evangelista Sagnelli; Mariantonietta Pisaturo (BMC, 2019)
Abstract Background At present, there is a continuous flow of immigrants from the south of the world to north-western countries. Often immigrants originate from areas of high-prevalence of viral hepatitis and pose a challenge to the healthcare systems of the host nations. Aims of this study is to evaluate the prevalence and virological and clinical characteristics of hepatitis C virus (HCV) infection in immigrants and the strategies to identify and take care of the immigrants infected with HCV. Main body We conducted an electronic literature search in several biomedical databases, including PubMed, Google Scholar, Scopus, Web of Science, using different combinations of key words: "HCV infection; chronic hepatitis C, immigrants; low-income countries". We included studies written in English indicating the epidemiological data of HCV infection in the immigrant population, studies that assessed the clinical presentation, clinical management and treatment with directly acting antiviral agent in immigrants, HCV infection is unevenly distributed in different countries, with worldwide prevalence in the general population ranging from 0.5 to 6.5%. In Western countries and Australia this rate ranges from 0.5 to 1.5%, and reaches 2.3% in countries of south-east Asia and eastern Mediterranean regions, 3.2% in China, 0.9% in India, 2.2% in Indonesia and 6.5% in Pakistan; in sub-Saharan Africa the prevalence of HCV infection varies from 4 to 9%. Immigrants and refugees from intermediate/high HCV endemic countries to less- or non-endemic areas are more likely to have an increased risk of HCV infection due to HCV exposure in their countries of origin. Because of the high HCV endemicity in immigrant populations and of the high efficacy of directly acting antiviral agent therapy, a campaign could be undertaken to eradicate the infection in this setting. Conclusions The healthcare authorities should support screening programs for immigrants, performed with the help of cultural mediators and including educational aspects to break down the barriers limiting access to treatments, which obtain the HCV clearance in 95% of cases and frequently prevent the development of liver cirrhosis and hepatocellular carcinoma.